Sphyraena stellata, a new barracuda from the Indo-Pacific, with redescriptions of S. helleri Jenkins, 1901 and S. novaehollandiae Günther, 1860 (Perciformes: Sphyraenidae) - Morishita, Satoshi; Motomura, Hiroyuki (Zootaxa, 2020)
A new barracuda, Sphyraena stellata, is described on the basis of 41 specimens [98.0–587.0 mm standard length (SL)] collected from the Indo-Pacific. The new species can be distinguished from all congeners in having the following combination of characters: one gill raker on first gill arch; pelvic-fin insertion located slightly before vertical through first dorsal-fin origin; pored lateral-line scales 134–141 (modally 137), total lateral-line scales 139–148 (146); scales above and below lateral line 15–17 (15) and 14–16 (15), respectively; snout comparatively short, its length 13.6–15.8 (mean 14.4) % SL; upper jaw short, its posterior tip not reaching to below anterior nostril, its length 10.0–12.2 (10.8) % SL; eye small, orbit diameter and depth 4.3–7.0 (4.9) and 3.9–5.6 (4.5) % SL, respectively; anal-fin base shortish, its length 6.9–8.1 (7.5) % SL; last dorsal- and anal-fin ray lengths 4.0–5.6 (4.7) and 3.6–5.6 (4.6) % SL, respectively; anus not close to anal-fin origin, anterior and posterior margins of former to anal-fin origin 7.5–11.9 (9.9) and 5.2–8.3 (6.8) % of head length, respectively; head sensory canal pores on suborbital area simple or slightly branched, their lowermost parts not close to margin of lacrimal bone, large smooth area lacking canal pores on mid-margin of lacrimal bone; two yellow stripes on lateral surface of body (remaining as black stripes in preserved specimens); and caudal fin gray. In addition, S. helleri Jenkins, 1901 and S. novaehollandiae Günther, 1860, both being closely related to the new species, are redescribed on the basis of 4 (243.3–545.8 mm SL) and 15 (270.8–598.0 mm SL) specimens, including holotypes, respectively, with new diagnostic characters proposed for both species.